PERANCANGAN SISTEM INFORMASI BERBASIS WEB PADA PUSAT REHABILITASI HEWAN ENDEMIK DKI JAKARTA ELANG BONDOL DI PULAU KOTOK, KEPULAUAN SERIBU - Muhammad Farhan (2021)
The Bondol Eagle is an endemic animal of DKI Jakarta which is currently protected because its number continues to decreased. Build a rehabilitation center in the Thousand Islands for Bondol Eagles is one of the efforts that made to maintain the survival of these animals. The rehabilitation center administrators recorded all the data that they used for the rehabilitation of the bondol eagle. However, at this time the rehabilitation center has not used a computer system to record all the data it has. The data recording activity at this rehabilitation center is still using the traditional system, which is recording in a book. Considering an importance of the task that rehabilitation center is to maintain the sustainability of the bondol eagle, their data should be computerized and recorded and processed with better media than those used today. The design of this website-based information system is intended to facilitate the management of the rehabilitation center in recording all documents and data so that the rehabilitation center has a better recording medium and is expected to replace the old recording media.